Oxygen Supersaturation Could Protect Reef‐Building Corals Against Acute Thermal Stress - Anieka J. Parry; Shannon G. Klein; Alexandra Steckbauer; Max S. Dhillon; Marcelle Muniz Barreto; Victoria C. Golding; Eleonora Re; Silvia Arossa; Manuel Aranda; Carlos M. Duarte (Global Change Biology, 2025)
Ongoing climate change is constraining the availability of molecular oxygen (O 2 ) on coral reefs. The field has recently invested considerable resources to quantify the effects of hypoxia on corals. However, drivers of reef oxygen decline will not only expose corals to more frequent episodes of hypoxia but also limit peak daytime oxygen levels. Here, we test the theory of oxygen‐mediated thermal performance on three reef‐building corals by comparing their thermal thresholds under three bulk seawater oxygen concentrations in low flow conditions: 10 mg O 2 L −1 , 6.5 mg O 2 L −1 , and 2 L −1 . We hypothesized that when the photosynthetic machinery of their microalgal symbionts was impaired, corals in higher oxygen treatments would use oxygen from the bulk water to supplement their heightened metabolic demands under heat stress, thereby increasing their thermal thresholds. The higher oxygen treatments of 10 and 6.5 mg O 2 L −1 increased the median lethal thresholds of two out of three corals by at least 0.4°C, while one species showed no detectable effect. The 10 mg O 2 L −1 treatment increased the thermal threshold of one species by a small but detectable extent of 0.2°C—a small effect, but one that is biologically meaningful given that marine heatwaves often push corals beyond limits by fractions of a degree. Across the three species, the onset of coral mortality coincided with the collapse of microalgal photosynthetic oxygen production, suggesting that reef‐building corals depend on oxygen from the bulk seawater to sustain aerobic metabolism during acute thermal stress. We hypothesize that the extent of this reliance is diffusion‐limited and strongly influenced by flow conditions. We posit that differences in coral susceptibility to heatwaves across reefscapes may be partially explained by oxygen regimes within microhabitats, emphasizing oxygen as a key regulator of reef health alongside temperature.